Transformation of The Tourism Business from Competition to Collaboration - Krismawintari, Ni Putu Dyah; Susrama, I Wayan; Putri, Andiena Nindya; Utama, I Gusti Bagus Rai (Technium Social Sciences Journal, 2021)
Cooperation is now widespread in most branches of industry. With the acceleration in the field of technological innovation and in the context of globalization, traditional and competitive promotion in business organizations is increasing, which is being replaced by collaborative relationships. This trend also applies to tourism, where fragmentation, multisector, and industry independence leads to links between international organizations and decision-making. But for many organizations, appearance is very important as part of effective collaboration in order to serve consumers better. There is also the view that the success of a collaborative relationship is an important organizational factor in the tourism industry in the long term.